Brazilian research panorama on information ergonomics and graphic design - Paschoarelli, Luis C. [UNESP]; Silva, João [UNESP]; Silva, Danilo [UNESP]; Bonfim, Gabriel [UNESP]; Medola, Fausto O. [UNESP]; Neves, Erica [UNESP] (Springer Nature, 2015)
With the emergence and easy access to new interfaces that are present and necessary to current daily life, a concern about the interface projects begins, and so, new research methods and analyzes emerge to support that growing demand. In seeking to understand how those researches are being treated in Brazil, this paper uses a bibliometric study concerning the area of Graphic Design and Informational Ergonomics in the largest conferences of Design in Brazil: “EGODESIGN/USIHC” and the “P&D Design”, in order to provide a panorama of the growth of research and study groups through the publications in the area. In addition it seeks to demonstrate the regions in the country which concentrates the focus on those themes and how Brazil is concerned with the issues related to the study and with the improvement of technological interfaces.
Keywords: Bibliometrics; Brazilian conferences; Graphic design; Informational ergonomics; Research